Hubungan Motivasi Berprestasi dengan Kinerja Pegawai di Dinas Pendidikan dan Kebudayaan Kabupaten Lima Puluh Kota - Wela Agustia Wulandari; Nelitawati Nelitawati; Rusdinal Rusdinal; Yulianto Santoso (Journal of Educational Administration and Leadership, 2021)
This study aims to obtain information on whether there is a relationship between achievement motivation and employee performance. The purpose of this study was to obtain information on: 1) employee performance, 2) achievement motivation, and 3) the relationship between achievement motivation and employee performance. The population of all civil servants and non civil servant employees in the Department of Education and Culture of Fifty Cities Regency is 89 people. The sample used was 47 people who were obtained based on the use of the Slovin formula based on the Proportional Stratified Random Sampling technique. The use of this research instrument is the use of a Likert Scale with 5 selected answers it have test for validity and reliability. Validity and reliability were tested with the help of SPSS 16.0 with the Product Moment correlation formula. The results of the analysis show 1) high category employee performance, namely 89.58%, 2) achievement motivation is in the high category 87.9%, and 3) there is a clear relationship between achievement motivation and employee performance in the Education and Culture Office of Lima Puluh Kota Regency. That is, r count 0.754> r table 0.288 and the t value is 7.717> t table 2,000 at the 95% confidence level, which shows a relationship between achievement motivation and employee performance. This means that achievement motivation is one of the factors that influence the performance of employees in the Education and Culture Office of Fifty Cities Regency.